Pengaruh antara Kualitas Pelayanan Dengan Keputusan Pengunjung Melalui Kepuasan di Rumah Makan Surabi 74, Larangan, Kota Tangerang, Provinsi Banten - Triono, Freddy; Amrullah, Amrullah; Maulana, Alifatqul; Pramudito, Pramudito; Abduh, Mohammad Syaltut (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
This study aims to analyze the influence of service quality on visiting decisions through customer satisfaction as a mediating variable at Surabi 74 Larangan Restaurant, Tangerang City. This study uses a quantitative approach with a path analysis method (path analysis) processed using SmartPLS software. The research sample consisted of 100 respondents who were Surabi 74 customers who had visited in the last six months. Data collection was conducted through distributing questionnaires with a five-point Likert scale. The results showed that service quality has a positive and significant effect on customer satisfaction, and has a direct and indirect significant effect on visiting decisions. Customer satisfaction is proven to be a mediating variable in the relationship between service quality and visiting decisions, meaning that the higher the customer satisfaction, the more likely they are to return. This finding emphasizes the importance of improving service quality that includes aspects of accommodation, responsiveness, assurance, empathy, and physical evidence in creating customer satisfaction and loyalty. Based on these results, it is recommended that restaurant managers improve service standards through employee training, maintaining cleanliness, and providing a varied menu to maintain customer satisfaction and interest in visiting in the future. Keywords: service quality, customer satisfaction, visiting decisions